Oral Apis dorsata Forest Honey Reduces the Number of Pseudomonas aeruginosa Colonies in the Blood of Mice - A Muhammad Ilham M; Edward Pandu Wiriansya; Rezky Pratiwi L. Basri; Dwi Anggita; Yani Sodiqah (Sarana Ilmu Indonesia (Salnesia), 2026)
Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen with high antibiotic resistance, driving the need for alternative antibacterials such as forest honey (Apis dorsata), although in vivo evidence distinguishing preventive, curative, and supportive roles remains limited. This true experimental post-test-only study evaluated the effectiveness of Apis dorsata forest honey in inhibiting P. aeruginosa growth in a mouse model. Thirty female BALB/c mice were divided into five groups: preventive, curative, supportive, positive control (ceftriaxone), and negative control. Forest honey (0.02 mL/g body weight) was given orally, and P. aeruginosa (10³ CFU/mL) was inoculated intraperitoneally. Bacterial colony counts from blood cultures showed that the negative control group had the highest mean count, while all honey-treated groups showed reduced colonies, especially the curative and supportive groups. The Kruskal–Wallis test revealed significant differences between groups (p = 0.01). In conclusion, Apis dorsata forest honey was effectively in reducing the growth of P. aeruginosa in mice and shows potential as a complementary antibacterial agent, particularly for curative and supportive therapy.